2020
DOI: 10.1684/epd.2020.1201
|View full text |Cite
|
Sign up to set email alerts
|

How to understand and address the cultural aspects and consequences of diagnosis of epilepsy, including stigma

Abstract: Epilepsy is one of the most prevalent serious neurological diseases. It is unique, being the only severe and disabling neurological disease that is fully treatable in the majority of cases, but on the other hand, associated with stigma, prejudice and discriminatory practices, which negatively impact people's everyday life in important areas, such as access to education, employment, marriage and social integration. For centuries, people with epilepsy (PWE) were stigmatized in all societies, with the consequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 117 publications
1
26
0
1
Order By: Relevance
“…Felt stigma can be reported by the person with epilepsy themselves (b) Enacted stigma is the occurrence of discrimination solely on the basis of the disease 2 . Enacted stigma is usually discovered by investigating social prejudices against the person with epilepsy 3 . Felt stigma is far more prevalent than enacted stigma and has been shown to be associated with low level of education and knowledge about epilepsy, both in the people with epilepsy feeling stigmatized and in their peers contributing to stigma 2,4,5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Felt stigma can be reported by the person with epilepsy themselves (b) Enacted stigma is the occurrence of discrimination solely on the basis of the disease 2 . Enacted stigma is usually discovered by investigating social prejudices against the person with epilepsy 3 . Felt stigma is far more prevalent than enacted stigma and has been shown to be associated with low level of education and knowledge about epilepsy, both in the people with epilepsy feeling stigmatized and in their peers contributing to stigma 2,4,5 …”
Section: Introductionmentioning
confidence: 99%
“…stigma is usually discovered by investigating social prejudices against the person with epilepsy. 3 Felt stigma is far more prevalent than enacted stigma and has been shown to be associated with low level of education and knowledge about epilepsy, both in the people with epilepsy feeling stigmatized and in their peers contributing to stigma. 2,4,5 Studies have also revealed that stigma affects the quality of life more than clinical variables like seizure types and frequency, and side effects of drugs.…”
mentioning
confidence: 99%
“…Frequent generalized seizures have numerous medical and social consequences, e.g., increased risk of injuries and fractures, progressive memory disorders, progressive cognitive impairment, and increased risk of mental disorders. The social consequences of drug-resistant epilepsy include social stigmatization, job loss, the costs of treatment of the co-morbidities and complications of epilepsy, and the costs of long-term institutional care [7].…”
Section: Introductionmentioning
confidence: 99%
“…People with epilepsy have been denied employment and education, and they face barriers to marriage, parenthood, and other aspects of social life. 7,8 Mortality is nearly threefold higher in people with epilepsy, compared with the general population. 9,10 Epilepsy ranks third among chronic neurologic diseases in terms of disability-adjusted years of life lost, 11 and sudden unexpected death in epilepsy is second only to stroke in terms of potential years of life lost among chronic neurological conditions.…”
Section: Introduction/ Backgroundmentioning
confidence: 99%
“…They also face discrimination and prejudice as consequences of widespread social stigma. People with epilepsy have been denied employment and education, and they face barriers to marriage, parenthood, and other aspects of social life 7,8 …”
Section: Introduction/backgroundmentioning
confidence: 99%